Triple band modified 90 degree Koch fractal H-slot microstrip antenna - Saeidi, T. (Institute of Electrical and Electronics Engineers Inc., 2017)
A tri-band fractal structure for Agriculture, WLAN and GSM band applications is presented. The desired resonances are 0.915, 1.8 and 2.45 GHz. This antenna consists of a modified 90 degree Koch fractal resonator, two layer substrates which are separated by an air gap layer and then fed through the SMA port and finally simulated on RT/Duroid 5880. Fractal shapes have been used to have a multi-band frequencies with a reduction in size. Furthermore, inductive and capacitive loadings have been applied though some stubs, gaps and two shorting posts to reduce the size. Thereafter, the equivalent circuit of the proposed antenna designed based on the literature. The uniqueness of the antenna is the miniaturized size (90 × 90 × 10mm3) compared to the first resonant frequency with high performance. The measured results performed on the performance of the proposed antenna, which has a good agreement with the simulation results. © 2016 IEEE.